Embedding Black Holes and Other Inhomogeneities in the Universe in Various Theories of Gravity: A Short Review - Valerio Faraoni (Universe, 2018)
Classic black hole mechanics and thermodynamics are formulated for stationary black holes with event horizons. Alternative theories of gravity of interest for cosmology contain a built-in time-dependent cosmological “constant” and black holes are not stationary. Realistic black holes are anyway dynamical because they interact with astrophysical environments or, at a more fundamental level, because of backreaction by Hawking radiation. In these situations, the teleological concept of event horizon fails and apparent or trapping horizons are used instead. Even as toy models, black holes embedded in cosmological “backgrounds” and other inhomogeneous universes constitute an interesting class of solutions of various theories of gravity. We discuss the known phenomenology of apparent and trapping horizons in these geometries, focusing on spherically symmetric inhomogeneous universes.